Efektivitas Media Audio Visual Berbasis Kearifan Lokal untuk Meningkatkan Literasi Budaya Siswa - Novitasari, Laily; Nura Aziza, Ella Rahma; Ariani, Puput; William, Nanda; Ika Puspita, Ari Metalin (Scholarly Journal of Elementary School, 2024)
Education has a big role in determining the progress or decline of a nation. Education is very necessary for every human being as a means of developing the values that exist within humans such as social, moral, religious and cultural values. Based on the results of observations, it was found that cultural literacy among students in elementary schools is still low. The aim of this research is to see the influence of the effectiveness of local wisdom-based audio visual media on increasing cultural literacy in elementary schools. The research method used in this research is quantitative with a quasi-experimental type. The sampling technique used in this research used saturated sampling, because all members of the population were used as research subjects. The instruments in this research used observation questionnaires and tests. The data analysis technique in this research uses an independent sample t-test with the help of SPSS 25.0 software. The research results show that audio-visual media based on local wisdom is effective in increasing cultural literacy in elementary schools. This is shown based on the results of different tests that there are differences in the understanding of cultural literacy before and after the use of audio-visual media based on local wisdom. So it can be concluded that there has been an increase in students' cultural literacy after using audio-visual media based on local wisdom.